2021
DOI: 10.1002/ccr3.5046
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma presenting as fulminant myocarditis mimicking COVID‐19 pneumonia

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Likewise, Wu et al detailed a case involving two middle-aged males with acute myocarditis and cardiogenic shock, necessitating an intra-aortic balloon pump (IABP) and ECMO for life support, ultimately unmasking the presence of a pheochromocytoma (19). In the same vein, Rojbi I et al documented a case of a 40-year-old female with symptoms suggestive of fulminant myocarditis and COVID-19 pneumonia, later attributed to a pheochromocytoma (20). These cases collectively reiterate the diagnostic hurdles posed by pheochromocytoma mimicking fulminant myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Wu et al detailed a case involving two middle-aged males with acute myocarditis and cardiogenic shock, necessitating an intra-aortic balloon pump (IABP) and ECMO for life support, ultimately unmasking the presence of a pheochromocytoma (19). In the same vein, Rojbi I et al documented a case of a 40-year-old female with symptoms suggestive of fulminant myocarditis and COVID-19 pneumonia, later attributed to a pheochromocytoma (20). These cases collectively reiterate the diagnostic hurdles posed by pheochromocytoma mimicking fulminant myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Even though pheochromocytoma is a rare condition, if a young patient presents with unexplained cardiac dysfunction, we should consider pheochromocytoma [ 7 ]. The prognosis of pheochromocytoma-induced cardiac diseases depends on early diagnosis and treatment [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…As just one example, recent studies provide indirect evidence that succinate-dependent cytokine response may be a central feature of the severe- and long-COVID that hallmarks a subset of SARS-CoV2 infections. In fact, there is some overlap between the symptoms of complex II deficiency and some of the unusual symptoms of COVID ( 183 , 184 , 185 ). Cell-permeable diethyl succinate boosts viral load ( 186 ), while metabolomics identified that succinate accumulation profoundly increases with disease severity ( 187 ).…”
Section: Succinate Signaling Regulation Of Transcription and Cell Fatementioning
confidence: 99%